Cultural Da'wah of Antar Pinang Pulang Memulangkan Tradition in Sambas Malay Society, West Kalimantan - Mualimin Mualimin; Ari Yunaldi; Sunandar Sunandar; Alkadri Alkadri (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2018)
Marriage is a basic human need, so in certain societies it becomes sacred tradition. The sacredness of marriage is manifested in the series of customs that are required to be carried out. The sacredness of the marriage is believed in society as the Sambas Malay community in West Kalimantan. In Sambas Malay, This tradition is popular as the tradition of Antar Pinang Pulang Memulangkan, which has been an important part in the customs of marriage until today. This tradition is not an empty tradition without meaning, instead it has a very high meaning and is a cultural da'wah with the internalization of Islamic teachings in everyday life. This research focuses on the design of cultural da'wah in the tradition of Antar Pinang Pulang Memulangkan. Using interpretive paradigms, with phenomenological methods and anthropological-sociological approach, this study found: first, the tradition of Antar Pinang Pulang Memulangkan is an effort to internalize Islamic teachings to strengthen four main aspects of the Muslim lives, namely 1) human relations with their creators. 2) suitable for human biological needs. 3) human relations in the family. 4) human relations with society in general. Second, an interesting approach by synergizing non-verbal messages through symbols and verbal messages through the language class in poetry, and suitable to meet the fundamental interests of humans makes this tradition of Antar Pinang Pulang Memulangkan as a model in the development of cultural da’wah.Perkawinan merupakan kebutuhan mendasar manusia sehingga pada masyarakat tertentu menjadi tradisi yang sakral. Sakralitas perkawinan diantaranya diwujudkan dengan rentetan adat istiadat yang diharuskan untuk dilaksanakan. Sakralitas perkawinan tersebut diyakini oleh masyarakat Melayu Sambas Kalimantan Barat. Pada Melayu Sambas dikenal tradisi antar Antar Pinang Pulang Memulangkan yang hingga saat ini menjadi bagian penting dalam tahapan adat istiadat pernikahan. Tradisi ini bukan tradisi yang kosong tanpa makna, tetapi justru memiliki makna yang sangat tinggi dan merupakan dakwah kultural dengan adanya internalisasi ajaran Islam dalam kehidupan sehari-hari. Penelitian ini terfokus pada desain dakwah kultural pada tradisi Antar Pinang Pulang Memulangkan. Menggunakan paradigma interpretif, dengan metode fenomenologi dan pendekatan antropologis-sosiologi, penelitian ini menemukan: Pertama, tradisi Antar Pinang Pulang Memulangkan merupakan upaya internalisasi ajaran Islam untuk memperkuat empat aspek utama dalam kehidupan umat Islam yaitu 1) hubungan manusia dengan penciptanya. 2) pemenuhan kebutuhan biologis manusia. 3) hubungan manusia dalam keluarga. 4) hubungan manusia dengan masyarakat secara luas. Kedua, pendekatan yang menarik dengan mensinergiskan pesan non verbal melalui simbol dan pesan verbal melalui bahasa kias dalam pantun, serta mampu menyentuh kepentingan mendasar manusia menjadikan tradisi Antar Pinang Pulang Memulangkan sebagai model dalam pengembangan dakwah kultural.